2003
DOI: 10.1111/j.1467-842x.2003.tb00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex in Australia: Autoerotic, esoteric and other sexual practices engaged in by a representative sample of adults

Abstract: Objectives: To describe the prevalence of a range of autoerotic and other non-coital sexual practices among Australians. Method: Computer-assisted telephone interviews were completed by a representative sample of 10,173 men and 9,134 women aged 16-59 years (response rate 73.1%). Respondents were asked whether in the past year they had:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 22 publications
(23 reference statements)
7
44
1
1
Order By: Relevance
“…We cannot explain the reason for the higher prevalence of USBs in men, but there are some studies demonstrating that unconventional sexual activities, such as group sex, finger stimulation of the anal region, oral stimulation of the anal region ("rimming"), use of vibrators or other fetish objects, sadomasochist games and use of the internet with sexual purposes, are more prevalent among men than among women. 3,14,15 Studies indicate an association between lower educational level and risky sexual behaviors 16 and paraphilias, 17 similar to what was found for individuals with USB.…”
Section: Discussionmentioning
confidence: 54%
“…We cannot explain the reason for the higher prevalence of USBs in men, but there are some studies demonstrating that unconventional sexual activities, such as group sex, finger stimulation of the anal region, oral stimulation of the anal region ("rimming"), use of vibrators or other fetish objects, sadomasochist games and use of the internet with sexual purposes, are more prevalent among men than among women. 3,14,15 Studies indicate an association between lower educational level and risky sexual behaviors 16 and paraphilias, 17 similar to what was found for individuals with USB.…”
Section: Discussionmentioning
confidence: 54%
“…Janus and Janus (1993) showed that about 14% of male and 11% of female responders in the United States had personal experience with sadomasochistic (SM) sexual practices and about 8-10% of responders had some SM ''toys'' at their homes. An Australian study showed that 2% men and 1.4% women had during last 6 months participated in SM activities (Richters, Grulich, de Visser, Smith, & Rissel, 2003). Preferences for BDSM activities in the Czech Republic were studied by an Internet trap method (Jozífková & Flegr, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Men and women report markedly different patterns of sexual initiation, sexual practice, sexual difficulties, sexual coercion and sexual satisfaction. 9,[13][14][15][16] While the intersection of gender and sexuality has been the subject of much research, the gender differentials observed here warrant further exploration.…”
Section: Patterning Of Sexual Practice In Australiamentioning
confidence: 83%